Molecular simulations of ion channel gating - Pipatpolkai, T (2021)
Ion channels are membrane proteins that facilitate ion permeation across the membrane down the concentration gradient. Recently, many structures of the ion channels were solved using cryo-electron microscopy. An advancement in structural determination and computational power has enabled ion channels to be thoroughly investigated at the molecular level using molecular dynamics (MD) simulation. Here, I used a range of methods, including coarse-grained MD, free energy perturbation (FEP) and atomistic MD simulation, to study the gating mechanisms of two ion channels, the ATP- sensitive K (KATP) channel and the Transmembrane 16A (TMEM16A) channel. I used CG-FEP to determine the binding affinity of phosphatidylinositol-4,5- bisphosphate (PIP2) to the KATP channel and investigate how insulin secretory disorder effects channels PIP2 affinity. In the light of collaborative experimental studies, I have also proposed the gating mechanism of how PIP2, an activator of the channel, may compete, with ATP, an inhibitor of the KATP channel. Last, I have determined an additional gate at the outer pore of the TMEM16A channel, which is the binding site of the biphasic drug anthracene-9-carboxylate (A9C). Together, the work in this thesis has demonstrated the power of MD simulation to investigate the gating mechanisms of multiple ion channels and their interactions with the allosteric modulators.